Nursing students and health literacy: The effect of region and programme level. (January 2020) - Balmer, Deborah; King, Anna; Moloney, Willoughby; Moselen, Emma; Dixon, Robyn
Abstract: Low levels of health literacy have been associated with poor health outcomes. If an organisation does not have a health literate workforce, it cannot be expected to create a healthcare service that supports the development of health literacy among its users. The aim of this cross-sectional study was to determine the health literacy profiles of undergraduate student nurses over year groups and between regions. The collaborative study employed an anonymous online survey using the Health Literacy Questionnaire which investigated the health literacy profiles of 845 undergraduate student nurses from eight universities in four regions from mid-2014 to early 2016 with co-investigators in each of the universities. Results show specific significant changes in health literacy profiles as a function of year level across the four regions; for example, in the Ability to find good health information. Different regions have different health literacy profiles; however, all could be improved. The results from this study provide specific direction to educators on what student health literacy may look like upon graduation as well as challenge current assumptions. Graduating nurse professionals have a role in mediating and sponsoring a health literate health system as well as being part of supporting patients' health literacy. Highlights: Describes the development of health literacy (HL) in student nurses. Student health literacy strengths vary across domains of the HLQ measure. HL variations are a function of both geographical location & year level. Provides specific HL domains that could be tackled to improve graduands' HL.